2011
DOI: 10.1029/2011gl048681
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice loss enhances wave action at the Arctic coast

Abstract: [1] Erosion rates of permafrost coasts along the Beaufort Sea accelerated over the past 50 years synchronously with Arcticwide declines in sea ice extent, suggesting a causal relationship between the two. A fetch-limited wave model driven by sea ice position and local wind data from northern Alaska indicates that the exposure of permafrost bluffs to seawater increased by a factor of 2.5 during 1979-2009. The duration of the open water season expanded from ∼45 days to ∼95 days. Open water expanded more rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(214 citation statements)
references
References 27 publications
(32 reference statements)
4
197
0
1
Order By: Relevance
“…This also adds perspective to the trend of OWD increase of 0.5-1 d a −1 observed by Barnhart et al (2014) for coastal cells in the Laptev Sea with significant trends over the entire 1979-2012 SSM/I data set. Overeem et al (2011) show that open water duration has been increasing along the Alaskan Beaufort Sea coastline from icy to ice-free over decades based on SSM/I ice cover calculations. In our case, most likely, the warm Lena River waters are likely to additionally support local seasonality via early break-up, because of generally thinner sea ice (Spreen et al, 2011) and earlier spring floods (Federova et al, 2009).…”
Section: Changes In Environmental Parametersmentioning
confidence: 99%
“…This also adds perspective to the trend of OWD increase of 0.5-1 d a −1 observed by Barnhart et al (2014) for coastal cells in the Laptev Sea with significant trends over the entire 1979-2012 SSM/I data set. Overeem et al (2011) show that open water duration has been increasing along the Alaskan Beaufort Sea coastline from icy to ice-free over decades based on SSM/I ice cover calculations. In our case, most likely, the warm Lena River waters are likely to additionally support local seasonality via early break-up, because of generally thinner sea ice (Spreen et al, 2011) and earlier spring floods (Federova et al, 2009).…”
Section: Changes In Environmental Parametersmentioning
confidence: 99%
“…Recent research has suggested that Arctic coastal erosion is generally restricted to a few months of open water during which waves can attack the coast and promote erosion Overeem et al 2011;Lantuit et al 2012). Sea-ice coverage has declined for the entire Arctic over the past four decades (Førland et al 2009), and Svalbard in particular is known to have lower sea-ice coverage due to the warm Atlantic Waters which flow past the western coast and enter into fjords (Å dlandsvik & Loeng 1991;Nilsen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These passive sea ice products have been used in numerous studies of Arctic climate and impacts of climate change encompassing: impacts on coastal erosion (Overeem et al, 2011), effects on wildlife such as polar bears (e.g., Stirling and Parkinson, 2006), relationship to greenhouse gas emissions (Johannessen, 2008), possible influences on midlatitude climate (e.g., Overland et al, 2010;Liu et al, 2012;Francis and Vavrus, 2012), model evaluations (e.g., Adams et al, 2011;Jahn et al, 2012), data assimilation (e.g., Lindsay and Zhang, 2006), and assessment of model projections Overland, 2009, 2012). The data have of course also been used to directly analyze time series of Arctic sea ice trends and variability (e.g., Bjørgo et al, 1997;Meier et al, 2007;Comiso and Nishio, 2008;Stroeve et al, 2011;Cavalieri and Parkinson, 2012).…”
Section: Introductionmentioning
confidence: 99%